Preparation And Characterization Of Novel Iron (III) HydroxidePaper Mill Sludge Composite Adsorbent For Chromium Removal - Ali Yaraş; Hasan Arslanoğlu (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This work deals withthe removal of Cr (III) and Cr (VI) from synthetic solutions via a novelcomposite adsorbent prepared by precipitating iron (III) hydroxide on papermill sludge (PMS). To obtain Fe(OH)3 loaded PMS, -8+16 mesh fractionof PMS was saponified with NaOH solution, then iron (III) chloride wasimpregnated, hydrolyzed in NaOH solution and dried. The influences of pH, time,initial concentration and temperature on removal of Cr (III) and Cr (VI) wereexamined and it was determined that Cr (VI) removal occurs simultaneously witha reduction reaction. Maximum removal yields for Cr (III) and Cr (VI) occurredat approximately pH = 5 and the adsorption achieved equilibrium in 90 min. Cr(VI) adsorption ratio decreases while Cr (III) removal percentage increaseswith raising in temperature. Experimental results are consistent with Langmuirisotherm. Adsorption capacities of Cr (III) and Cr (VI) were calculated as8.49, 10.14, 12.62 mg/g and 7.64, 5.39 and 4.17 mg/g for 25, 40 and 55 °C,respectively. Enthalpy changes for Cr (III) and Cr (VI) were calculated as24.67 kJ/mol and -12.46 kJ/mol, respectively. These results demonstrated thatthe adsorption phenomenon of Cr (III) and Cr (VI) are endothermic andexothermic.